Fabrication Of Bismuth Ferrite/Poly(O-Phenylenediamine) Based Carboxymethyl Cellulose Hydrogel And Its Photocatalytic Performance Towards Methyl Orange Under Direct Sunlight - Zaahari, Nor Atilia Athira (2022)
CMC/BFO/PoPD (CBP) hydrogel film is successfully prepared by impregnating of the optimized BFO/PoPD into carboxymethyl cellulose (CMC) hydrogel with condition of molar ratio of BFO:oPD was 1:0.4 in 0.1 M HCl and the molar ratio of ammonium persulphate (APS) to oPD was 1.5:1 for degradation of methyl orange (MO) under direct sunlight.